KONDISI KARANG SCLERACTINIA DI PERAIRAN BULUTUI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - M. Takdir Umanailo; Inri M Manembu; Hermanto WK Manengkey; carolus P Paruntu; Rosita A Lintang; Wilmy E Pelle (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Hard coral is one of the main components of this forming coral reef ecosystem. Bulutui waters have coral reef ecosystems that have a direct role as a source of livelihood for people around these waters. However, there are non-environmentally friendly human activities such as fishing using explosives or chemical solutions that cause coral reef damage. The aimed of this research was to find out the condition of hard coral’s percentage cover and to described the frequency of hard coral’s occurance therefore it’s could be representative data at this location. Coral data was collected by using PIT (Point Intercept Transect) method. The value of percentage cover of hard corals at Bulutui waters are 20.58% and the value is categorized damaged. The total frequency of hard coral’s occurance at station 1 are 66 and dominated by Coral Submassive (CS), at station 2 are 23 and dominated by Coral Massive (CM), at station 3 are 18 and dominated by Coral Foliose (CF) and then at station 4 are 140 and dominated by Coral Foliose (CF).Keywords: Percentage Cover, Scleractinia Coral, Bulutui Waters, PIT Methods.